Differences in growth and biomass allocation of Adiantum flabellulatum and A. capillus-veneris as a result of light and water availability. Issue 4 (2nd October 2017) - Liao, J. X.; Zhang, H.; Mo, L.; Huang, Y. Q.; Sun, Y. J.; Li, Y. Q.
Abstract: Most Adiantum species favor shaded and moist conditions, but A. flabellulatum prefers ample sunlight. To better understand such differences and elucidate possible ecophysiological mechanisms, we grew A. flabellulatum and A. capillus-veneris, a famous indoor ornamental species, under three light (360, 180, and 90 μmol photons m -2 s -1 ) and two soil moisture (15.5 and 10.3% w/w) conditions and compared their dry matter production and allocation, leaf traits, and relative growth rate (RGR). For A. flabellulatum, reduced light availability significantly increased chlorophyll (Chl) content but decreased total mass and RGR. In A. capillus-veneris, total leaf area (LA), specific leaf area (SLA), and leaf area ratio (LAR) increased, but total mass and RGR did not differ as light availability decreased. Under drought stress, both species decreased LA, LAR, and Chl content. However, A. flabellulatum increased root allocation, and its total mass and RGR remained almost unaffected, whereas in A. capillus-veneris, biomass allocation did not change but total mass and RGR decreased significantly. Relative to A. capillus-veneris, A. flabellulatum exhibited lower LA, SLA, LAR, Chl content, and RGR under the same conditions, but higher root allocation, lower leaf allocation, and similar RGR under high light and drought conditions. These results suggested that different adaptive strategies exist between the two species. A. flabellulatum is relatively superior in drought tolerance but inferior in shade tolerance, allowing it to persist in habitats with low soil moisture and high light availability. A. capillus-veneris can capitalize on available resources and hence promote its growth in low light canopy conditions.